Change in base rate and its effects on the economy in the last 20 years in Hungary - Halmosi Tímea; Голмоші Т.; Belovecz Mária; Беловец М.; Tangl Anita; Тангл А. (ФОП Сабов А. М., 2019)
Abstract. The main purpose of the whole economic policy is to make the stable and sustainable growth in the long run. The Central Bank can be at the back of this with a calculable and transparency monetary policy for keep the inflation on a low-level. The home law for Central Bank bases on this recognition. The law prescribes for MNB (Hungarian Central Bank) the reach and keep the price stability as a primary purpose in accord with the international practice and the laws of EU. The central banks, who follow the inflation target tracking set a numerical aim for inflation correlate with the change of Consumer Price Index. They vary the level of the base rate in a way that the aim for inflation comes true. It is made a prognosis from the probable inflation regularly. If this prognosis is above the aim considerably, it is stiffened the monetary shape. It is mean that it is increased the rates. If the prognosis is under the aim, it is relieved the monetary shape, so it is decreased the rates.
Зміна облікової ставки та її вплив на економіку Угорщини останні 20 років
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00007679
Keywords: base rate; Hungary; economy